Dampak Pandemi Covid-19 terhadap Peningkatan Partisipasi Santri dan Penjualan Produk Koperasi Pondok Pesantren Al-Basyariyah Bandung - Anne Lasminingrat; Rakhmia Nalibratawati (Jurnal Maps (Manajemen Perbankan Syariah), 2023)
The Al-Basyariyah Islamic Boarding School Cooperative based in the city of Bandung, has also been affected by the Covid-19 pandemic, but in a positive aspect. In the form of a consumption cooperative, engaged in the sector of fulfilling the daily needs of students, from clothing, food, educational needs, to laundry, plus the closure of students' access to the outside environment and vice versa, making the Kopontren the only means of meeting daily needs, both for students, teachers, and those who are part of the Al-Basyariyah Islamic Boarding School environment. This study aims to explain the impact of the Covid-19 pandemic on the participation of students as service users and its effect on the sale of cooperative products in the Al-Basyariyah Islamic Boarding School environment. The research technique uses a survey method with the determination of respondents using the Slovin formula and an estimated number of respondents of 230 respondents. The analytical design used was a paired t-test or paired t-test, namely to test member participation and product sales before and after the Covid-19 pandemic.